Pengaruh Bauran Pemasaran Terhadap Keputusan Nasabah Mengambil KPR Syariah Bank Jatim Syariah Surabaya - Qorizah, Alfia; Prabowo, Prayudi Setiawan (Jurnal Ekonomika dan Bisnis Islam, 2019)
This research is aimed to observe the influence of marketing mix towards customers’ decision to get Islamic home financing in Bank Jatim Sharia Branch Surabaya. The type of research is qualitative with associative clausal approach. The number of the sample for this research is 50 respondents and the type of sampling used is simple random sampling. Technique of analysis used is multiple linear regression with the help of SPSS 23 program. The result shows that partially, the marketing mix variables which influence significantly towards customers’ decision in using the product Islamic home financing variable are, promotion, place, people, and promise. Meanwhile, variables which do not influence the customers’ decision are product, price, process, physical proof and patience. Simultaneously, marketing mix variables influence customers’ decision significantly.